Efficacy of octahedral molecular sieves for green and sustainable catalytic reactions - Lucas, Nishita; Gurrala, Lakshmiprasad; Halligudi, S. B. (Molecular Catalysis, 2020)
Sustainability and Green Chemistry has emerged as catchphrase in modern era and researchers worldwide have embraced it as new paradigm of development. In this context identifying potential materials able to curb multiple grave issues thus contributing towards sustainability is vital. Catalytic materials are quite potent for addressing current social, economic and environmental problems like harnessing alternative energy source, pollution prevention/remediation and manufacturing of commodity chemicals. Thus, the present review accentuates the efficacy of porous octahedral molecular sieves (OMS) as catalyst for such environmentally important reactions. It discusses about structural importance of OMS and their applications for green and sustainable catalytic reactions. Finally, the limitations are highlighted and future perspectives are presented which will ameliorate its catalytic utilization in energy and environmental domains.
Keywords: catalytic transformations; Lignocellulosic biomass; octahedral molecular sieves; platform chemicals; renewable feedstock